Plasma concentration of amitriptyline and metabolites after resuscitation from cardiopulmonary arrest following an overdose: A case report. Issue 2 (15th December 2020) - Ando, Motozumi; Tamura, Ryo; Nakasako, Shinji; Takimoto, Satsuki; Ariyoshi, Koichi; Yamaguchi, Marie; Sakizono, Kenji; Eto, Masaaki; Fukushima, Shoji; Sugioka, Nobuyuki; Hashida, Tohru
Abstract: It may need to pay attention to the sustention of moderate cardiotoxicity and delayed elevation of plasma 10‐hydroxynortriptyline level in severe amitriptyline overdose case. Abstract : It may need to pay attention to the sustention of moderate cardiotoxicity and delayed elevation of plasma 10‐hydroxynortriptyline level in severe amitriptyline overdose case.